Non-adherence to ivermectin in onchocerciasis-endemic communities with persistent infection in the Bono Region of Ghana: a mixed-methods study - Kenneth Bentum Otabil; María-Gloria Basáñez; Blessing Ankrah; Emmanuel John Bart-Plange; Theophilus Nti Babae; Prince-Charles Kudzordzi; Vera Achiaa Darko; Abdul Sakibu Raji; Lydia Datsa; Andrews Agyapong Boakye; Michael Tawiah Yeboah; Joseph Nelson Siewe Fodjo; et al. (BMC Infectious Diseases, 2023)
Abstract Background The World Health Organization has proposed that onchocerciasis elimination (interruption) of transmission be verified in 12 (approximately a third) endemic countries by 2030. The strategy to reach this goal is based on ivermectin Mass Drug Administration (MDA) with high geographical and therapeutic coverage. In addition to coverage, high levels of treatment adherence are paramount. We investigated factors associated with ivermectin intake in an area of Ghana with persistent Onchocerca volvulus infection. Methods In August 2021, a cross-sectional mixed-methods study was conducted in 13 onchocerciasis-endemic communities in the Bono Region of Ghana. Individuals aged ≥ 10 years were invited to participate in a questionnaire survey. A total of 48 focus group discussions and in-depth interviews with 10 community drug distributors and 13 community leaders were conducted. Results A total of 510 people participated in the study [median age: 32, interquartile range 30 (20‒50) years]; 274 (53.7%) were females. Of the total, 320 (62.7%) declared that they adhered to each treatment round and 190 (37.3%) admitted they had not taken ivermectin during at least one MDA round, since becoming eligible for treatment. Of 483 participants with complete information, 139 (28.8%) did not take ivermectin during the last round (March 2021), and 24 (5.0%) had never taken ivermectin (systematic non-adherers). Reasons for not taking ivermectin included previous experience/fear of side-effects, being absent during MDA, pregnancy, the desire to drink alcohol, and drug distribution challenges. Being male, having good knowledge and perception of the disease, and not having secondary or higher level of formal education were significantly associated with higher odds of ivermectin intake. Conclusions A relatively high level of non-adherence to ivermectin treatment was documented. There is a need for targeted educational and behavioural change campaigns to reverse these trends and ensure a steady course toward meeting onchocerciasis elimination targets in Ghana.